Sistem inventaris berbasis web di workshop Teknik Elektro - Amrozi, M Ali; Widyassari, Adhika Pramita (Jurusan Informatika STTR Cepu, 2023)
This inventory information system provides several facilities that can be used by the manager, including: input of item data, delete item search item, and item data inventory report, item inventory system at the Electrical Engineering Workshop - STTR CEPU aims to facilitate the laboratory manager in data collection goods, both complementary goods or consumables, which are web-based, for example inputting new goods or damaged goods, can be done online, and the number of goods will be automatically entered in the database, without us adding up the goods manually, search results for item data more easily fast, accurate, and the results of reports that can be downloaded in PDF type, and can be printed. The purpose of the research is to increase efficiency in managing computerized laboratory inventory so that it can support the performance of lab managers, Archives and Electrical Engineering workshops, Designing this application using language programming PHP, CSS, HTML, Windows 10 64 bit Operating System, Visual Studio Code software version 1.69.1, Xampp Server version 1.7.7, PHP version 7.3.2, Bootstrap version 5.0, Google Chrome, 000webhost. The test results show that 77% of this application can run and make it easier for the Cepu-Sttr Laboratory manager. Keywords: Inventory System, Laboratory, Cepu Sttr